The Holocaust Averted : An Alternate History of American Jewry, 1938-1967 - Gurock, Jeffrey S., 1949- (Book collections on Project MUSE., 2015)
In The Holocaust Averted, Jeffrey Gurock imagines what might have happened to the Jewish community in the United States if the Holocaust had never occurred and forces readers to contemplate how the road to acceptance and empowerment for today's American Jews could have been harder than it actually was.